Analisis Teknik Gerak Tari Tradisional Dengan Menggunakan Ilmu Kinesiologi (Jurnal Seni Tari, 2020)
Dancing knowledge in Indonesia is evolving. In the beginning, dance was used as a ritual. But with formal education dance interdisciplinary with other subject, such as science. Positivistic dance science is contrary with Indonesian traditional dance which is dominant with ethnicity, and that makes kinesiology not too well developed in Indonesia. The aim of this article is to study traditional dance movement through kinesiology. The author uses qualitative method with critical and creative analytical, also studying the theory regarding traditional dance movement and kinesiology. The finding of this article is kinesiology can be used to analyze traditional dance movement technique regarding the joint movement and the driving muscle. Traditional dance movement practicing also about 'feel management' training, so the particular 'feel' is still enjoyable for the audience. Identical movement with different appreciation will produce different movement, so it takes balance in practicing movement technique and 'feel management' training. In order to support movement technique training, artist and dance teacher can study it through kinesiology. Keywords: Traditional dance, kinesiology, analysis, and movement technique